Psychotropic polypharmacy in people with neuropsychiatric symptoms referred to an Australian dementia support service - Atee, Mustafa; Andreotta, Matthew; Morris, Thomas; Alford, Marie (2022)
Background: Despite limited evidence, psychotropics, such as antipsychotics are commonly used to treat neuropsychiatric symptoms (NPS) in people living with dementia. There are safety concerns on the use of antipsychotics, but co-prescribing multiple classes of psychotropics (psychotropic polypharmacy) may have a greater and more serious harm to this group. This includes sedation-induced falls, delirium, hospitalizations, and mortality. In Australia, people with significant NPS, such as agitation and aggression can be referred for free 24/7 support and advise to a national behavior dementia-specific support service known as Dementia Support Australia (DSA). The aim of this study is to describe the prevalence of psychotropic polypharmacy in DSA referrals.